Bartalinia kevinhydei (Ascomycota), a new leaf-spot causing fungus on teak (Tectona grandis) from Northern Thailand - Tibpromma, Saowaluck; Karunarathna, Samantha C.; Mortimer, Peter E.; Xu, Jianchu; Doilom, Mingkwan; Lumyong, Saisamorn (Phytotaxa, 2020)
This paper introduces an interesting new fungus, isolated from teak (Tectona grandis) leaf-spots, collected in Chiang Rai Province, Thailand. Phylogenetic analysis of combined ITS and LSU sequence data together with morphological studies confirmed that the disease was caused by a Bartalinia species, distinct from described taxa. Detailed description, photomicrographs and a phylogenetic tree are provided to showcase the taxonomic placement of the new species, B. kevinhydei. Geographical distribution of Bartalinia species is also provided. This is the first report of a Bartalinia species growing on teak, and also the first report for Bartalinia in Thailand.